Determinasi Factor Struktur Modal Dan Dampaknya Terhadap Nilai Perusahaan (Studi Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Nuratul Amaliah; Ronny Malavia Mardani; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the Determination of Factors of Capital Structure and Its Impact on Corporate Value Case study in food and beverage companies. The independent variables in this study are profitability, company size, company growth and capital structure, while the dependent variable in this study is firm value. This type of research is empirical research with the data used are secondary data obtained by searching for and collecting annual report data obtained from the website. The population in this study are food and beverage companies listed on the Indonesia Stock Exchange period 2017-2019 with a total of 26 companies. The sample selection technique was obtained by a sample of 14 companies. To solve the problem in this study using normality test, classic assumption test, multiple linear regression test and hypothesis test. The results of data analysis show that: There is a positive influence on profitability, firm size, and capital structure variables on firm value, while company growth has a negative effect on firm value in food and beverage companies. Keywords: Profitability, Company Size, Company Growth, Capital Structure Against Company Value